2016
DOI: 10.1136/neurintsurg-2016-012386
|View full text |Cite
|
Sign up to set email alerts
|

Admission systolic blood pressure and outcomes in large vessel occlusion strokes treated with endovascular treatment

Abstract: Higher admission SBP is an independent predictor of increased FIV and lower likelihood of 3-month FFO in patients with ELVO treated with EVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 26 publications
3
51
0
2
Order By: Relevance
“…Previous studies investigating BP relation with outcome, specifically in acute ischemic stroke, also showed that both low and high BP were associated with poor functional outcome. Of the 3 previous studies on BP and outcome after IAT, one did not investigate the relation of BP with functional outcome, 19 the second study found that higher SBP was associated with poor functional outcome after IAT, 20 and the third study found SBP not to be a predictor of outcome after multivariable analysis. 21 The second and the third study did not test for nonlinearity.…”
Section: Baseline Bp and Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating BP relation with outcome, specifically in acute ischemic stroke, also showed that both low and high BP were associated with poor functional outcome. Of the 3 previous studies on BP and outcome after IAT, one did not investigate the relation of BP with functional outcome, 19 the second study found that higher SBP was associated with poor functional outcome after IAT, 20 and the third study found SBP not to be a predictor of outcome after multivariable analysis. 21 The second and the third study did not test for nonlinearity.…”
Section: Baseline Bp and Outcomementioning
confidence: 99%
“…18 Three studies suggest that high BP is a risk factor for poor outcome and SICH in patients treated with IAT. [19][20][21] It is currently unknown whether BP interacts with IAT effect. The recent focused AHA/ASA guideline update about IAT provide no guidance whether a specific BP should be considered a contraindication for IAT, or whether a certain BP should be treated before IAT.…”
Section: Strokementioning
confidence: 99%
“…SBP on admission has already been associated with an increased infarct volume and lower rate of 3-month favorable outcome in patients with large vessel occlusion treated with ET 18. BG on admission, even in non-diabetic patients, together with failure in glycemia drop in the first 48 hours, are both significant predictors of 90-day poor outcome and death19; moreover, high BG on admission is predisposed to HT 20.…”
Section: Discussionmentioning
confidence: 99%
“…For the patients presenting 6–12 hours from symptom onset, additional imaging selection criteria are used such as Alberta Stroke Program Early CT Score (ASPECTS) ≥6 on brain CT and/or good collaterals on CTA. LVO was diagnosed on pretreatment CTA using standard criteria 20. Brain CT head and CTA were performed on a 64-slice scanner.…”
Section: Methodsmentioning
confidence: 99%